Diagnostic analysis of adult neuronal ceroid lipofuscinosis caused by CLN6 gene mutation: a case report - Yubo Hu; Haochen Sun; Qin Jiang; Juan Wang; Shugang Zhang; Xingjian Lin (Clinical Parkinsonism & Related Disorders)
Neuronal ceroid lipofuscinosis is a rare lysosomal storage disorder that is difficult to distinguish from other diseases with similar clinical symptoms in its early stages. This article analyzes and summarizes the diagnostic process of a family affected by adult neuronal ceroid lipofuscinosis caused by CLN6 gene mutation. We collected clinical data from a 48-year-old female patient with neuronal ceroid lipofuscinosis who visited Nanjing Brain Hospital in March 2024. She has presented with corresponding symptoms since 2020. The patient underwent whole exome sequencing (WES) and other examinations. WES showed that both the patient and her elder brother, who exhibited similar symptoms of walking instability, were homozygous for a mutation in the CLN6 gene. This variant (c.856C > T: p.Leu286Phe) has not been previously reported and is classified as a Variant of Uncertain Significance (VUS) based on current American College of Medical Genetics and Genomics/Association for Molecular Pathology(ACMG/AMP) guidelines. Both of the patient’s parents displayed normal phenotypes but were found to have heterozygous mutations in the CLN6 gene. Additionally, no nuclear inclusion bodies were found in the patient’s skin tissue.